Efficacy of Tuohy Needle in Oocytes Collection from Excised Mare Ovaries - F. Cremonesi; K. Anderson; A. Lange-Consiglio (Veterinary Medicine International)
Two methods have been described to recover oocytes from equine follicles in excised ovaries: aspiration and scraping. Aim of this work was to develop an effective method for collecting equine oocytes using Tuohy needle and comparing this technique to aspiration and scraping, with or without tunica albuginea removal. This hollow hypodermic needle, usually employed for inserting epidural catheters, is designed with a slightly curved tip, shaped similar to a small curette. In unpeeled ovaries, the recovery rates of Tuohy needle group was higher (𝑃<.05) than in the 16 g needle aspiration and in the scraped ovaries (57% versus 36% and 47%) while the rate of cumulus-intact oocytes was higher than aspiration (46.9% versus 39.36%) but lower than scraping (46.97%) (𝑃<.001). In unpeeled ovaries there was significant difference in maturation rate of oocytes recovered by Tuohy needle in respect to peeled ovaries (58.54% versus 50.17%, resp.). Combination of aspiration and scraping by Tuohy needle allows a faster and reliable collection of oocytes suitable for horse IVM.